Point-of-care ultrasound at Role 1: is it time for a rethink?. Issue 6 (20th May 2020) - Duncan, Patrick G A; Mackey, J
Abstract : Introduction: The past 20 years have seen a rapid increase in point-of-care ultrasound (POCUS) use in the prehospital sphere. However, in the British Army there is no POCUS capability in the Defence Primary Healthcare (DPHC) or deployed Role 1 setting. POCUS can improve diagnostic capability, influence management decisions and transfer destination, and is a useful triage tool in mass casualty management. Method: A survey on POCUS use was sent to 279 clinicians working in the Role 1, civilian prehospital and Defence Primary Healthcare environments. Questions explored current levels of experience and training, indications for use and attitudes towards roll out. Results were analysed using a mixed methods approach. Results: There were 124 respondents (279 recipients; 44.4% response rate). 74.2% (92 respondents) had no experience of using POCUS while 9.7% (12 respondents) were classed as frequent users. The four most common indications for prehospital POCUS were abdominal, cardiac and lung imaging and vascular access. The majority of respondents felt that POCUS would add value in the deployed Role 1 environment; this was even more evident in the frequent user group. Common concerns were difficulty maintaining currency, governance burden and uncertainty over impact on management. Conclusion: The majority of doctors surveyed feel that POCUS would add value at Role 1 and is a capability that should be developed. The authors will watch with interest the progress of Project MORPHO.